2007
DOI: 10.2169/internalmedicine.46.1901
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings of Papillary Thyroid Carcinoma with Hashimoto's Thyroiditis

Abstract: Objective Papillary thyroid carcinoma (PTC) sometimes occurs with Hashimoto's thyroiditis (HT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 15 publications
3
41
1
1
Order By: Relevance
“…Asymptomatic DTD, especially HT, is known to be significantly related to the occurrence of thyroid malignancy compared with normal thyroid. 9,10 Ohmori et al 11 reported that PTC with HT has a prevalence of 5.5%, which is higher than that of PTC without HT. Therefore, we suggest that the high incidence of asymptomatic DTD reflects thyroid malignancy in 310 patients (91.2%, 310/340) as the main cause of thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic DTD, especially HT, is known to be significantly related to the occurrence of thyroid malignancy compared with normal thyroid. 9,10 Ohmori et al 11 reported that PTC with HT has a prevalence of 5.5%, which is higher than that of PTC without HT. Therefore, we suggest that the high incidence of asymptomatic DTD reflects thyroid malignancy in 310 patients (91.2%, 310/340) as the main cause of thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gender The incidence of HT in PTCs according to gender was compared in 23 studies (3,4,5,6,7,14,15,19,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38). HT in PTCs was observed in 1677 of 7346 (23%) female patients and in 180 of 573 (11%) male patients.…”
Section: Clinicopathologic Characteristics Of Ptcs With Htmentioning
confidence: 99%
“…In addition, the clinicopathologic characteristics of PTCs with concomitant HT have not been definitely proposed (3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). Therefore, the present meta-analysis was conducted to clarify the relationship between PTCs and histologically proven conventional HT and to investigate the clinicopathologic features of PTCs with coexistent HT.…”
Section: Introductionmentioning
confidence: 97%
“…The ultrasonography findings were, however, not diagnostic and it was therefore considered by the authors that it is important to make a careful examination if thyroid carcinoma is suspected in patients with HT because HT presents a variable picture on ultrasonography. 48 Therefore the conclusion is still rather uncertain in that the diagnosis of thyroid cancer in patients with HT is subject to many pitfalls and errors, despite advances in technology. The clinicians must use a spectrum of criteria and careful follow-up of the patients for the final diagnosis.…”
Section: Does Radiation Induce Thyroid Autoimmunity?mentioning
confidence: 99%